Combined feedback/feedforward active control of vibration of beams with ACLD treatments: numerical simulation and experimental implementation - César M. A. Vasques (2005)
This paper concerns the numerical simulation of feedback, adaptive feedforward and hybrid (combined feedback/feedforward) control systems on the active control of vibrations of beams with Active Constrained Layer Damping (ACLD) treatments. For the simulation a 1-D beam finite element (FE) model with an arbitrary number of elastic, piezoelectric and viscoelastic layers attached to both sides of the beam is utilized. The damping behavior of the viscoelastic layers is considered by a Laplace transformed Anelastic Displacement Fields (ADF) method. The analyzed case study regards the disturbance rejection of an aluminium beam with a pair of surface mounted ACLD patches. In the design and simulation of the control system a Single-Input Single-Output (SISO) configuration with the output being the velocity at one point of the beam and the input being the control voltage applied into the piezoelectric constraining layers is considered. The case study allows to assess and discuss the outcomes and drawbacks of the feedback and feedforward controllers when used individually and the advantages of the hybrid controller.